EFEKTIFITAS PEMBINAAN TERHADAP KOMPETENSI GURU TK DALAM PROSES PEMBELAJARAN MENGGUNAKAN ZOOMMEETING - Elly Asnarosi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The main objective of this research was to improve teachers' ability in learning by implementing guidance by supervisors using zoom meetings. During the current covid-19 pandemic, many learning processes were still disrupted so that the learning process became less effective. As a result, the ability of teachers and students decreased. Therefore, there was a need for guidance by supervisors through zoom meetings because it was still not possible for face-to-face meetings. The form of this research is school action research which aims to improve and develop teachers' ability in the learning process. This research was conducted in a kindergarten in Dumai, and the research subject was the teacher. The results showed an increase that occurred after the coaching action for the teachers. It was evident from the percentage of coaching results with an 85% increase which was a quite large increase compared to the previous data. Then, for the results of observing teacher activities in the first cycle, data were found to be 55% with a fairly good category, then in the second cycle, 80% data was found in the very good category. Looking at the data, it can be seen that the teacher's abilities and teaching skills have been improved after learning reflection was carried out in the form of coaching actions by supervisors.